Conquerors tales of ancient & medieval conquests ; from the age of legions, empires and kings, 3000 years of conquest and rule - Matthews, Rupert 1961- (Carlton Books, 2009)
Looks at 13 of the most successful empire builders, up to the eighteenth century, that the world has ever seen. Each conqueror is detailed in turn; the scope of their conquests is examined together with the backgrounds to their careers and the results that followed after their deaths
Keywords: Conquerors / Biography / Juvenile literature; Kings and rulers / Biography / Juvenile literature; Conquerors; Kings and rulers; Biografie